K.H. Lanre Said: Ulama Pendidik dari DI/TII hingga Era Reformasi - Ilham Kadir (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2019)
This study aims to reveal the various aspects of life of K.H. Lanre Said, a great scholar, great educator whose services are so great in fostering generations through the educational institutions he founded, namely Darul Huffadh Islamic Boarding School located in Tuju-Tuju Kajuara Bone, South Sulawesi. This research is a type of qualitative descriptive research with a historical approach. Data collection techniques used are interviews, document studies, literature studies, and field observations. The results of this study reveal various aspects of life and the path of da'wah and the messages of K.H. Lanre Said, as an educating scholar, and the perfect hafizh of al-Qur'an. He is a Bugis cleric who can be used as an example from various sides, from the scientific aspect, the power of memorization, to being a role model in life. K.H. Lanre Said became a real example of a Bugis ulama, spending his age in the midst of society by establishing educational institutions to educate the life of the nation, living simply as it is, and the messages are always actual to practice. K.H. Lanre Said's main capital in affirming itself as a guiding ulama to the right path is the depth of knowledge, real practice, good behavior (ampe-ampe madeceng), avoiding the word lies even if only joking, prioritizing public rather than personal interests, and always willing and sincere in doing. With this power, the position of K.H. Lanre Said in the middle of the Bone community in general and the Tuju-Tuju community in particular is irreplaceable.